(untitled) (Research, Society and Development, 2022)
Objective: To provide pharmaceutical care through pharmaceutical services aimed at elderly patients with asthma treated in an outpatient pharmacy. Method: Interventional, cross-sectional and prospective study, carried out from July 2019 to December 2019. During pharmaceutical consultations, pharmacotherapeutic data were collected, problems related to medications were identified and pharmaceutical services were performed through organizational and educational interventions. Results: 26 users completed the follow-up, most of them female (84.62%), residing in Belém (84.62%), high school education (46.15%), retired occupation (69.23%). More than half (53.85%) were overweight, (61.53%) did not practice physical activity. The most prevalent comorbidities were hypertension (65.41%) and dyslipidemia (42.36%). The most prevalent Drug Related Problems were poorly treated health problem (20.28%), and incorrectly administered drugs (17.39%). After the different interventions, there was an improvement in adherence to drug treatment (p<0.01), greater disease control (p<0.01), better lung function (p<0.01) and improvement in quality of life ( p<0.01). Conclusion: The practice of pharmaceutical care carried out through pharmaceutical services directly aimed at elderly patients with asthma significantly improved clinical and humanistic outcomes in